PDDL+ Planning with Events and Linear Processes - Coles, Amanda; Coles, Andrew (Proceedings of the International Conference on Automated Planning and Scheduling, 2014)
We present a scalable fully-automated forward-chaining planner capable of reasoning with PDDL+ events and linear processes. Processes and events model (respectively) continuous and discrete exogenous activity in the environment, occurring when certain conditions hold. We discuss the significant challenges posed in creating a planner that can reason with these, and present novel state-progression and consistency enforcing techniques that allow us to meet these challenges. We present results showing that our new planner, using PDDL+ models, is able to solve realistic expressive problems more efficiently than the state-of-the-art alternative: a compiled PDDL 2.1 representation with continuous numeric effects.